Strategi Marketing Pondok Pesantren dalam Meningkatkan Mutu Layanan Pendidikan (Studi Kasus Pondok Pesantren Raudhatul Mujawwidin Kec. Rimbo Bujang Kab. Tebo) - Barokah, Al (Jurnal Ekonomi Manajemen Sistem Informasi, 2023)
This research is descriptive-qualitative with a direct approach to fieldwork, data collection techniques were carried out by; 1). Observation, 2). Interview, 3). Documentation. After conducting in-depth research, the following specific results were found: 1) The marketing strategy used at the Raudhatul Mujawwidin Islamic Boarding School, namely Holistic Marketing Kothler with the application of values to the exemplary nature of Rasulullah SAW; 2) Raudhatul Mujawwidin Islamic Boarding School's efforts to improve the quality of education services; and 3) The results of the marketing strategy of the Raudhatul Mujawwidin Islamic boarding school in improving the quality of education services found that: 1). The majority of stakeholders are satisfied with the results of the quality of education offered, alumni are accepted at universities, Islamic boarding schools and are actively involved in the community. 2). A good image is created, through the media Raudhatul Mujawwidin is also known by word of mouth, moreover there are 48 fostered institutions and also sending students to the regions every year in community service programs.